HOW DEMOGRAPHIC AND POLITICAL KNOWLEDGE SHAPE VOTERS EXPECTATION TOWARD CANDIDATES CHARACTER - Satrio, Hendri Budi; Mursitama, Tirta Nugraha; Alamsjah, Firdaus; Pradipto, Yosef Dedy (International Journal of Psychosocial Rehabilitation, 2020)
Leaders have so many character. Indonesian has also expectation for their leader. This article will show us the leader’s character that Indonesia have expectation for according to the demographic and political knowledge of the people. The research conducted in 1 city and 3 districts in Indonesia, namely Simalungun District, North Sumatra Province, Bandung District, West Java Province, Tangerang Selatan City, Banten Province and Pacitan District, East Java Province. There were 400 respondents for each area, thus, involved a total 1600 respondents. Face-to-face interviews were conducted in January until February 2020. The result will inform us the character of leaders that Indonesian have hope for since Joko Widodo’s character become new phenomena in Indonesia.